The Effect of Product Quality, Price and Promotion on The Purchase Decision of Ms Glow Cosmetics Branch in Gresik - Moch Agung Setiabudi; Sukaris Sukaris (INNOVATION RESEARCH JOURNAL, 2022)
ABSTRACT This research was motivated by the fast-growing skin care industry, especially MS Glow. As a local brand whose name continues to grow until now, it has established many beauty clinics throughout Indonesia. At the same time, efforts are needed to continue to survive and compete with other skin care products. Moving on from these issues, this research is here with the aim of studying further about product quality, price, and promotion of purchasing decisions at MS Glow Gresik Branch. The population in this study were visitors to the beauty clinic at the Randuagung branch. From this population, this study obtained 90 samples who became respondents. The sampling technique was purposive sampling, namely the data collection technique used by distributing questionnaires. The results of the study show that product quality has no effect on purchasing decisions. However, prices and promotions influence purchasing decisions. Keywords: MS Glow, Product Quality, Price, Promotion, and Purchase Decision.